Correlates of Interorganizational Service Coordination in Community Corrections. (April 2016) - Welsh, Wayne N.; Prendergast, Michael; Knight, Kevin; Knudsen, Hannah; Monico, Laura; Gray, Julie; Abdel-Salam, Sami; Malvini Redden, Shawna; Link, Nathan; Hamilton, Leah; Shafer, Michael S.; Friedmann, Peter D.
Because weak interagency coordination between community correctional agencies (e.g., probation and parole) and community-based treatment providers has been identified as a major barrier to the use of evidence-based practices (EBPs) for treating drug-involved offenders, this study sought to examine how key organizational (e.g., leadership, support, staffing) and individual (e.g., burnout, satisfaction) factors influence interagency relationships between these agencies. At each of 20 sites, probation/parole officials ( n = 366) and community treatment providers ( n = 204) were surveyed about characteristics of their agencies, themselves, and interorganizational relationships with each other. Key organizational and individual correlates of interagency relationships were examined using hierarchical linear models (HLM) analyses, supplemented by interview data. The strongest correlates included Adaptability, Efficacy, and Burnout. Implications for policy and practice are discussed.